Great Wall Structure Plan Training for Military Base Defense of Anti-Aircraft Design Construction Architects with United Principle in Pancasila - Pamuji, Wirawan; Mimin Suriadi; Irwan Suriaman (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
Defense Construction for Military Base in a Builder perspective is very enormous to develop in structuring main foundation for rejecting enemy attack in sudden circumstance. Great Wall of China was built to hold enemy attack with large amount of enemy in any direction with anti-aircraft assemble. The Research applies Research and Development Instrumental method to develop Structure Plan towards Defense in military purpose about holding attack from enemy sudden arrival. Due that great wall was build in a single assemble construction in structure all materials, it is important to explain that the construction of castle was designed to hold the enemy as all the soldiers could conduct and have cooperation ahead within Pancasila Philosophy